Implementation of Group Discussion Method as an Effort to Increase Students' Faith in the Messenger of Allah SWT at Elementary School 091567 Bah Jambi - Dirmaya, Eva; Hidayanti, Sri (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the effectiveness of using group discussion methods in increasing students' faith in the Messenger of Allah SWT in students of SDN 091567 Bah Jambi. This method is considered effective in helping students understand and internalize Islamic teachings, especially related to faith in the Messenger of Allah SWT. This study uses a qualitative approach with a classroom action research design. The results of the study indicate that group discussions have a positive impact on students' understanding and faith in the Messenger of Allah SWT, marked by an increase in students' enthusiasm and understanding of the material being taught. Group discussions also strengthen relationships between students and encourage collaboration in understanding religious teachings. These data were obtained through observations during open classes. The data obtained were analyzed descriptively and quantitatively, by describing the number and percentage of active, enthusiastic and enthusiastic students who increased their enthusiasm for learning. The results of observations on student activities were discussed during reflection, and used as a basis for determining the next learning model. Students were very active and enthusiastic in using the discussion method to achieve an increase of 10% in the pre-cycle and 15% in cycle 1 and cycle 2.